Quantifying non-CO2 contributions to remaining carbon budgets - Jenkins, Stuart; Cain, Michelle; Friedlingstein, Pierre; Gillett, Nathan; Walsh, Tristram; Allen, Myles R. (Nature Publishing Group, 2021)
The IPCC Special Report on 1.5 °C concluded that anthropogenic global warming is determined by cumulative anthropogenic CO2 emissions and the non-CO2 radiative forcing level in the decades prior to peak warming. We quantify this using CO2-forcing-equivalent (CO2-fe) emissions. We produce an observationally constrained estimate of the Transient Climate Response to cumulative carbon Emissions (TCRE), giving a 90% confidence interval of 0.26–0.78 °C/TtCO2, implying a remaining total CO2-fe budget from 2020 to 1.5 °C of 350–1040 GtCO2-fe, where non-CO2 forcing changes take up 50 to 300 GtCO2-fe. Using a central non-CO2 forcing estimate, the remaining CO2 budgets are 640, 545, 455 GtCO2 for a 33, 50 or 66% chance of limiting warming to 1.5 °C. We discuss the impact of GMST revisions and the contribution of non-CO2 mitigation to remaining budgets, determining that reporting budgets in CO2-fe for alternative definitions of GMST, displaying CO2 and non-CO2 contributions using a two-dimensional presentation, offers the most transparent approach.
Keywords: Climate and Earth system modelling; Climate change; Climate-change mitigation